Non-Work Behaviour as A Mediator in The Relationship Between Quality of Work Life and Subjective Career Success - Nur Fatihah, Abdullah Bandar; Khairuddin, Idris; Farida, Abdul Halim; Surena, Sabil; Nik Norsyamimi, Md Nor; Helmi, Sumilan; Ling, Nyuk Ping (UNIMAS Publisher, Universiti Malaysia Sarawak, 2019)
Universities are organisations which generate scientific knowledge in contributions to the development of society. University performance is important to be the evaluation on the level of economic development in a country. It is also the ability for the citizens to compete in the global economy which can affect the productivity of the country. Thus, it is necessary to maintain and improve the levels of the quality of work life (QWL) so that academicians serving as the bedrocks of every academic institution are able to exhibit high performance. As a result, this may increase the sustainable economic development. In the case of Malaysia, married academicians often face work and family life conflict due to their multiple roles (Achour, Mohd Yusoff, & Mohd Nor, 2013). It is difficult for married academicians to balance work demands with personal and family responsibilities when they are overloaded with office work and household work and faced spouse-related issues. It becomes even more challenging where they have children. They also face these conflicts when they perceive poor working conditions such as inflexible work schedules and long working hours (Achour et al., 2013). Therefore, the management of academic institutions should introduce specific measures and initiatives to improve the QWL of married academicians in order to assist them to achieve work-life balance and their commitment besides attaining organisational objectives in an effective manner. While previous studies have examined QWL and subjective career success, there is a research gap examining how non work orientation affects the relationship with QWL and subjective career success. Non work behaviour define as an experiences in different spheres of life (e.g., having a career, being a member of a family, engaging in time to pursue personal interests, or community service). This study sought to identify and clarify these relationships. This study examined the relationship between the quality of work life (QWL) and subjective career success through the mediating effect of non-work behaviour (Community, family and personal life). Self-administered surveys were used to collect data from 200 married academicians in selected Public Institutions of Higher Learning in Sarawak. Data was analysed using Analysis of Moment Structures (AMOS) for Structural Equation Modelling (SEM). Results indicated that there were positive significant effects between QWL, non-work orientation, and career success. A partial mediation effect of non-work behaviour was established on the relationship between the QWL and career success. The findings implied that one way to increase the subjective career success of employees is through the provision of flexible policies that allow employees to participate in community work, attend to family matters and time off for personal development. These results will be important to the management of academic institutions and human resources practitioners who are interested in enhancing the career success of married academicians.